Transient Transformation of Potato Plant (Solanum tuberosum L.) Granola Cultivar Using Syringe Agroinfiltration - Yesy John Mba’u; Iriawati Iriawati; Ahmad Faizal (AGRIVITA, Journal of Agricultural Science, 2018)
Genetic transformation has been used as an alternative approach to improve the quality and the productivity of potato plant. In this study, different conditions have been set up to optimize transient GFP (Green Fluorescence Protein) expression in potato cv. Granola. Leaves of potato were infiltrated with Agrobacterium tumefaciens strain C58C1 harboring pK7FWGF2 vector with a nuclear-targeted GFP by simple pressure. GFP signals allowed simple evaluation of transformation efficiency which were indicated by GFP expression in nucleus of leaf cells in infiltratedareas. The results showed that leaf position, co-cultivation time, optical density and the presence of acetosyringone significantly affected the transformation efficiency. The fourth terminal leaves from four-week old plants were the optimum age for transformation. Furthermore, the highest transient transformation efficiency was obtained upon 48 h post infiltration at an OD600 = 0.8, and the presence of 200 μM acetosyringone. In conclusion, the developed protocol will be useful to study gene function as well as to generate stable transformation of this potato cultivar.